Numerical Study on the Self-Pulsation Characteristics of LOX/GH2 Swirl Coaxial Injector - Wentong Qiao; Chengkai Liang; Luhao Liu; Shaoyan Wang; Bingbing Zhang; Xiaocong Yang; Lijun Yang; Qingfei Fu (International Journal of Aerospace Engineering)
To investigate the self-pulsation characteristics of a liquid-centered swirl coaxial injector with liquid oxygen (LOX) and gas hydrogen (GH2) as the working mediums under supercritical condition, a numerical simulation was employed. The transient simulation of the flow and injection process of cryogenic propellant was carried out using the RNG k−ε turbulence model, VOF model, and Peng-Robinson equation of state. The frequency spectrum of calculated pressure oscillation agreed with the experimental data. The amplitude-frequency characteristics of recess region, LOX, and GH2 paths when self-pulsation occurs were analyzed. The effects of operating parameters, such as the flow rate of LOX or GH2 and the initial GH2 temperature, on the self-pulsation, were evaluated specifically. Results reveal that the self-pulsation results from the periodic variation of pressure and velocity caused by the periodic blocking of annular gas by the liquid sheet. The dominant frequencies of pressure oscillation in the recess region, upstream of LOX, or GH2 path are diverse. But for the points in each region, the dominant frequency is about the same. When the LOX/GH2 mixing ratio increases, the liquid sheet thickness and the number of liquid filaments increase. The position where filaments are massively broken into droplets moves further downstream. For the same mixing ratio, the flow rate of LOX has a greater impact on the atomization features. The pressures corresponding to low or high frequency increase when the initial GH2 temperature raises. The higher temperature would shift the dominant oscillation between the low and high regimes.